W poszukiwaniu modelu praktyk nauczycielskich – z doświadczeń i refleksji nauczyciela akademickiego (pedagoga praktyk) - Małgorzata Wójcik (Problemy Wczesnej Edukacji)
The theoretical basis of the teaching practice model is based on the tradition of praxis, critical theory and the psychopedagogics of creativity. Teacher’s actions are determined by the knowledge of a reflective – critical praxis and are understood to be wise and ethical, requiring application and interpretation of the theory. In their teaching practice, teachers should use both instrumental knowledge, that is téchnē and create new and valuable solutions. All this should begin with the very first teaching experiences of the students, especially in the real-life situations offered by the teaching practice. This means the process of education in the practices should be organized by an academic teacher (practice teacher). The idea is that students do not learn directly from their practice, but progress in their teaching practice from the application of theory to creation and verification of their own, new and valuable solutions. The Practice teacher supports students by organizing group and individual educational dialogue and pedagogical discourse on the practice material, and learning through research and action. The effectiveness of the teaching practice is determined by research conducted by an academic teacher using a variety of qualitative research techniques.